Artificial Intelligence in Cyberspace: Between Danger and Innovation (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of the article is to examine the impact of artificial intelligence on cybersecurity and to explore both the risks and the opportunities it presents. The article examines the primary forms of criminal use of AI in cyberspace, as well as develops effective methodologies for its application in the process of investigation, prevention, and analysis of these socially dangerous actions.[Methodology/approach/design] The authors employed an interdisciplinary approach combining methods from legal science, economics, and information technology in their work. Numerous scientific works on AI's characteristics, its role in digitization, and its use in criminal investigations have been noted. These studies offer suggestions, particularly for law enforcement agencies, financial institutions, and cybersecurity organizations. However, they are mainly theoretical and overlook new cyber threats and techniques used by cybercriminals with AI. In contrast, the authors analyzed illegal activity websites and forums, including cyberspace, using AI capabilities. They used cognitive methods to analyze how AI is used in cybercrimes, both as an auxiliary and primary tool. Content analysis methodology facilitated a systematic review of web content related to AI-enabled cybercrimes. The comparative-legal method compared AI-enabled cybercrimes to similar crimes without AI. Reviewing scientific articles, books, and conference proceedings helped understand AI, cybersecurity, and law enforcement. Case studies examined specific instances of AI in cybercrime, aiding in real-life prevention and investigation. The systematic method ensured a comprehensive examination of previous studies, identifying trends, challenges, and development prospects in AI and cybersecurity. By adopting this multifaceted and innovative approach, the authors were able to provide a more comprehensive and nuanced understanding of the emerging landscape of AI-assisted cybercrime. This research not only contributes to the academic discourse but also offers practical insights for law enforcement agencies, policymakers, and cybersecurity professionals working to combat these evolving threats.[Findings] The utilization of AI in the realm of cybercrimes unveils new prospects for the criminals themselves, as well as offers opportunities for effective combat and investigation of these crimes through AI. It is emphasized that the application of AI in crime investigations aids in refining the processes of detection and analysis of cybercriminal activities, allowing for quicker identification of anomalies and response to them. However, despite AI's significant potential, its use necessitates a cautious approach and the development of ethical and legal standards. This is essential to avoid possible negative consequences and ensure balanced development in cybersecurity.